Design and Implementation of an Application for Deploying Vehicular Networks with Smartphones - P. Caballero-Gil; C. Caballero-Gil; J. Molina-Gil (International Journal of Distributed Sensor Networks)
A vehicular ad hoc network (VANET) is a wireless network that provides communications between nearby vehicles. Among the different types of information that can be made available to vehicles through VANETs, road traffic information is the most important one. This work is part of an experimental development of a wireless communication platform oriented to applications that allow improving road efficiency and safety, managing and monitoring road traffic, encouraging cooperative driving, and offering pedestrian services and other added-value uses. The proposed system consists of smartphones, sensors, and Wi-Fi hotspots 2.0, as well as complementary functionalities including access to network infrastructure via 3G, GPRS, and 4G. The developed wireless network prototype allows taking advantage of the potential benefits of VANETs. At the same time, the use of smartphones does not require large money investments either in public or restricted areas. The first implementations with smartphones have been useful to test the behaviour of the proposal in a real environment. We have also implemented a large-scale simulation by using NS-2 simulator. From the obtained data, we have estimated the minimum requirements necessary for the correct working of a VANET and the problems that can happen in case of possible attacks or communication overhead.